1997
DOI: 10.1080/00071669708418027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of avgard™ treatment on the microbiological flora of poultry carcases

Abstract: 1. The efficiency of the AvGard (or Assur-Rince in the USA) trisodium phosphate poultry carcase decontamination process was evaluated during both manual and industrial trials against total aerobic mesophilic count (TAMC), thermotolerant coliforms, Pseudomonas, Enterobacteriaceae, Campylobacter, Listeria monocytogenes and Salmonella. 2. The TSP treatment proved to have significant effects on the bacterial decontamination of poultry neck skin, lowering the contamination by a factor of about 10 for TAMC and of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…Moreover, del Río et al (2007) reported reductions of various bacterial species by about 0.5 (B. thermosphacta, enterococci) or 1.0-1.5 orders of magnitude (lactic acid bacteria, Micrococcaceae, psychrotrophs, Pseudomonas). The great range of results obtained by Salvat et al (1997) might be explained by the treatment of carcasses at different points during slaughter, whereas those reported by Coppen, Fenner, and Salvat (1998) might be associated with the investigation of different plants. Direct comparisons of immersion and spraying with TSP were not performed in the evaluated studies, but immersion chilling tended to yield high reductions and those obtained for coliforms and E. coli (P4.0 log CFU ml À1 ) were especially striking (Fabrizio et al, 2002).…”
Section: Trisodium Phosphatecontrasting
confidence: 52%
“…Moreover, del Río et al (2007) reported reductions of various bacterial species by about 0.5 (B. thermosphacta, enterococci) or 1.0-1.5 orders of magnitude (lactic acid bacteria, Micrococcaceae, psychrotrophs, Pseudomonas). The great range of results obtained by Salvat et al (1997) might be explained by the treatment of carcasses at different points during slaughter, whereas those reported by Coppen, Fenner, and Salvat (1998) might be associated with the investigation of different plants. Direct comparisons of immersion and spraying with TSP were not performed in the evaluated studies, but immersion chilling tended to yield high reductions and those obtained for coliforms and E. coli (P4.0 log CFU ml À1 ) were especially striking (Fabrizio et al, 2002).…”
Section: Trisodium Phosphatecontrasting
confidence: 52%
“…In a previous paper (Salvat et al, 1997) Salmonella incidence in model demonstration trials was reported, together with results from the rst industrial broiler immersion installation in Europe (trial site 4). The former showed that the process was effective in an industrial context (controls: 71·4% of Salmonella positive carcases; treated: 7·3% of Salmonella positive carcases).…”
Section: Introductionmentioning
confidence: 93%
“…Bactericeae have also been reported [21]. Nevertheless, the suitability of using them as parameter to determine the efficiency of hygienisation is questionable since although they are usually associated with intestinal infections, they can be found in almost all natural habitats.…”
Section: Experiments 1: O 2 Controlmentioning
confidence: 99%